Polymorphisms Within the IQGAP2 and CRTAC1 Genes of Gannan Yaks and Their Association with Milk Quality Characteristics - Juanxiang Zhang; Guowu Yang; Xita Zha; Xiaoming Ma; Yongfu La; Xiaoyun Wu; Xian Guo; Min Chu; Pengjia Bao; Ping Yan; Chunnian Liang (Foods)
The IQ motif containing GTPase activating protein 2 (IQGAP2) gene functions as a tumor suppressor, reducing the malignant properties of breast cancer cells. The circulating cartilage acidic protein 1 (CRTAC1) gene, present in the whey protein fraction of dairy cows throughout lactation, is significantly correlated with fatty acids in milk. In this study, we investigated the correlation between single nucleotide polymorphisms (SNPs) in the IQGAP2 and CRTAC1 genes and milk quality traits in Gannan yaks, aiming to identify potential molecular marker loci for enhancing milk quality. Using the Illumina Yak cGPS 7K liquid chip, we genotyped 162 yaks and identified five SNPs in the IQGAP2 (g.232,769C>G, g.232,922G>C) and CRTAC1 (g.4,203T>C, g.5,348T>G, g.122,451T>C) genes. Genetic polymorphism analysis revealed that these five SNPs were moderately polymorphic and in Hardy–Weinberg equilibrium. An association analysis results showed that, at the g.232,769C>G locus of the IQGAP2 gene, the heterozygous CG genotype had significantly higher lactose content than the CC and GG homozygous genotypes (p < 0.05). Similarly, at the g.232,922G>C locus, the heterozygous GC and mutant CC genotypes significantly increased the contents of milk fat, lactose, and total solids (TS) (p < 0.05). In the CRTAC1 gene (g.4,203T>C, g.5,348T>G, g.122,451T>C), the mutant CC genotype significantly increased milk fat content, while the heterozygous TG genotype significantly increased lactose content (p < 0.05). In summary, mutations at the loci of g.232,769C>G, g.232,922G>C, g.4,203T>C, g.5,348T>G, and g.122,451T>C significantly elevated the lactose, milk fat, and TS content in Gannan yak milk, providing potential molecular marker candidates for improving Gannan yak milk quality.